Metacognition : What Roles Does It Play in Students’ Academic Performance? - Norehan, Binti Zulkiply; Mohamad Raduan, Bin Kabit; Kartini, Binti Abd Ghani (Common Ground Research Networks, 2008)
This paper discusses metacognition, defined as thinking about one’s own thinking, and its relation ship to student’s academic performance. A number of previous studies have shown that metacognition and intelligence were associated, and there fore suggested that students who have metacognition end to be successful learners. This paper also reports on a study investigating the relationship between students’ academic achievement and metacognitive awareness, which has been done at a private secondary school in Kuching. An established instrument by Schraw and Dennison’s Metacognitive Awareness Inventory is used for the purpose of this study.